The Relevance of Imam Al-Shafi’i’s Epistemological Thought in Fiqh Studies in the Digital Era - Agus Salim Lubis (South Sulawesi Education Development, 2026)
This study examines the relevance of Imam al-Shafi‘i’s epistemological thought to the development of contemporary Islamic jurisprudence in the digital era. It specifically explores the extent to which his methodological principles can support legal reasoning, maintain the authenticity of Islamic scholarship, and address the challenges arising from the rapid circulation of digital religious information. This study employed a qualitative library research design. Data were obtained from the works attributed to Imam al-Shafi‘i, classical Islamic jurisprudence literature, and contemporary scholarly studies concerning digital transformation in Islamic scholarship. The data were analyzed through content analysis by identifying, interpreting, and comparing the principal sources and methodological foundations of Imam al-Shafi‘i’s epistemology with current developments in digital Islamic jurisprudence. The findings indicate that Imam al-Shafi‘i’s epistemological framework, which is grounded in the Qur’an, Sunnah, ijma‘, and qiyas, remains methodologically relevant for addressing contemporary legal issues. His framework also provides a critical basis for assessing the validity of digital religious information, ensuring systematic legal reasoning, preventing unqualified interpretations, and preserving the authority of competent Islamic scholars. Imam al-Shafi‘i’s epistemological thought continues to offer a reliable foundation for the development of adaptive, systematic, and authentic Islamic jurisprudence in the digital age. Its application can strengthen scholarly authority and improve the credibility of contemporary digital fiqh discourse.